Desenvolvimento de uma plataforma de força para análise da performance biomecânica - Naves, Eduardo Lázaro Martins (2001)
Nowadays elite athletes from different kinds of sports are looking for an increase in their performance by using new methods and equipment which are available due to the great technological advance in the last few years. For this purpose, researchers worldwide are improving and developing new equipment and techniques to acquire and manipulate data for analyzing the performance of athletes. Included in this equipment used for analyzing the performance of athletes are the force plates which are used to quantify and analyze accurately the ground reaction forces when athletes are practicing some physical activity. This equipment is important because a strict analysis can be made during the training of athletes. Besides improving the performance of athletes this analysis can also prevent lesions during physical activities. Variables as force magnitude, position and direction can be obtained during the analysis process and they constitute a valuable information to professionals of the interdis-ciplinary field of biomechanics. In order to contribute to the vast field of biomechanics the author of this work have developed, with national technology, a system capable of acquiring and analyzing reaction forces during the practice of vertical jumps and weight lifting. The developed system is capable of providing the following parameters: the vertical component of the ground reaction force, the developed athlete power, the maximum ixX jump height, the mean power in a given interval of time, etc. The results show that the performance of the national system is comparable to international Systems.